Periplocymarin Plays an Efficacious Cardiotonic Role via Promoting Calcium Influx - Yun, Weijing; Qian, Lei; Cheng, Yanyan; Tao, Weiwei; Yuan, Ruqiang; Xu, Hu (Frontiers in Pharmacology, 2020)
Periplocymarin, which belongs to cardiac glycosides, is an effective component extracted from Periplocae Cortex. However, its cardiovascular effects remain unidentified. In the present study, injection of periplocymarin (5mg/kg) through external jugular vein immediately increased the mean arterial pressure (MAP) in anesthetized C57BL/6 mice. Ex vivo experiments using mouse mesenteric artery rings were conducted to validate the role of periplocymarin on blood vessels. However, periplocymarin failed to induce vasoconstriction directly, and had no effects on vasoconstriction induced by phenylephrine (Phe) and angiotensin II (Ang II). In addition, vasodilatation induced by acetylcholine (Ach) was insusceptible to periplocymarin. Echocardiography was used to evaluate the effects of periplocymarin on cardiac function. The results showed that the injection of periplocymarin significantly increase the ejection fraction (EF) in mice without changing the heart rate. In vitro studies using isolated neonatal rat ventricular myocytes (NRVMs) revealed that periplocymarin transiently increased the intracellular Ca2+ concentration observed by confocal microscope. But in Ca2+-free buffer, this phenomenon vanished. Besides, inhibition of sodium potassium-activated adenosine triphosphatase (Na+-K+-ATPase) by digoxin significantly suppressed the increase of MAP and EF in mice, and the influx of Ca2+ in cardiomyocytes, mediated by periplocymarin. Collectively, these findings demonstrated that periplocymarin increased the contractility of myocardium by promoting the Ca2+ influx of cardiomyocytes via targeting on Na+-K+-ATPase, which indirectly led to the instantaneous rise of blood pressure.